Lean startup for materials ventures and other science-based ventures: under what conditions is it useful?. (28th August 2015) - Harms, Rainer; Marinakis, Yorgos; Walsh, Steven T
Abstract: Materials-based ventures face a high degree of technology uncertainty and market uncertainty when engaging in the technology entrepreneurial process. Recently, the lean startup methodology (LSM) has been introduced to practice and education as an integrated approach on how entrepreneurs can resolve these uncertainties when starting up a business. While the literature provides examples of LSM's successful application in a range of application areas, its focus application tends to be on consumer software. The purpose of this article is to discuss the degree to which LSM can be applied to the context of technology entrepreneurship. We find that LSM has strengths in addressing market uncertainty, but is largely silent on addressing technology uncertainty. In situations of a low degree of technology readiness, strongly intertwined process and product innovation processes such as those common in materials translation, and of addressing business markets, LSM may not suffice. We discuss the case of competence leveraging as one where technology uncertainty is lower for materials companies and illustrate the benefits on LSM in this context.